Morpho-anatomical and SSR diversity in mutant gene pool of jute (Corchorus olitorius L.) - Satya, Pratik; Banerjee, Ruby; Ghosh, Swagata; Karmakar, P. G. (The Indian Journal of Genetics and Plant Breeding, 2016)
Characterization of induced mutants is gaining importance for increasing efficiency of mutation assisted plant breeding. In this study, phenotypic and genetic diversity of a set of 60 mutants of Corchorus olitorius (tossa jute), an important fibre yielding crop species were characterized using morphological traits related to fibre and biomass productivity, anatomical traits related to fibre distribution and development in the bark tissues of jute and simple sequence repeat (SSR) polymorphism. Morpho-anatomical diversity revealed high variability in the population, identifying mutant genotypes with superior fibre recovery and fibre anatomy traits. Ten of these mutants exhibited higher fibre recovery than a popular cultivar, JRO 204. A good number of mutants exhibited superior fibre anatomy characters like fibre wedge length, fibre wedge breadth and number of fibre cells per bundle than the cultivars. Twenty three SSR markers amplified a total of 53 alleles with polymorphism information content of 0.53. Six markers, MJM 006, MJM 432, MJM 489, MJM 566, MJM 569 and MJM 618 exhibited high resolving power (= 0.5). SSR marker based cluster analysis identified more genetic groups than morphogenetic classification, but association between genetic and phenotypic classification was low. For selection of parents for mutation assisted genetic improvement in jute, judicious use of both diversity measures for selection of parents would be more useful.